A two-component probability distribution function describes the mid-IR rmission from the disks of star-forming galaxies - Pathak, Debosmita; Leroy, Adam K.; Thompson, Todd A.; Lopez, Laura A.; Belfiore, Francesco; Boquien, Médéric; Dale, Daniel A.; Glover, Simon; Klessen, Ralf S.; Koch, Eric W.; Rosolowsky, Erik; Sandstrom, Karin M.; et al. (The astronomical journal, 2024)
High-resolution JWST-MIRI images of nearby spiral galaxies reveal emission with complex substructures that trace dust heated both by massive young stars and the diffuse interstellar radiation field. We present high angular (0.″85) and physical resolution (20-80 pc) measurements of the probability distribution function (PDF) of mid-infrared (mid-IR) emission (7.7-21 μm) from 19 nearby star-forming galaxies from the PHANGS-JWST Cycle 1 Treasury. The PDFs of mid-IR emission from the disks of all 19 galaxies consistently show two distinct components: an approximately lognormal distribution at lower intensities and a high-intensity power law component. These two components only emerge once individual star-forming regions are resolved. Comparing with locations of H ii regions identified from Very Large Telescope/MUSE Hα mapping, we infer that the power-law component arises from star-forming regions and thus primarily traces dust heated by young stars. In the continuum-dominated 21 μm band, the power law is more prominent and contains roughly half of the total flux. At 7.7-11.3 μm, the power law is suppressed by the destruction of small grains (including PAHs) close to H ii regions, while the lognormal component tracing the dust column in diffuse regions appears more prominent. The width and shape of the lognormal diffuse emission PDFs in galactic disks remain consistent across our sample, implying a lognormal gas column density N(H) ≈ 1021 cm−2 shaped by supersonic turbulence with typical (isothermal) turbulent Mach numbers ≈5−15. Finally, we describe how the PDFs of galactic disks are assembled from dusty H ii regions and diffuse gas and discuss how the measured PDF parameters correlate with global properties such as star formation rate and gas surface density.